South Africa : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2014)
This paper discusses findings of the Financial System Stability Assessment for South Africa. South Africa's financial sector operates in a challenging economic environment. Despite remarkable progress since the end of apartheid in 1994, South Africa still has one of the world's highest unemployment and income inequality rates. Slow economic growth since 2008 has further aggravated unemployment, real disposable income is stagnant, and households are heavily indebted. Relatively high capital buffers as well as sound regulation and supervision have helped mitigate the risks. Stress tests confirm the capital resiliency of banks and insurance companies to severe shocks but illustrate a vulnerability to liquidity shortfalls.